Single‐Nucleus RNA Sequencing Reveals That Gabra6+ Neurons in Prefrontal Cortex Promote the Progression of PTSD After Shockwave‐Induced TBI - Xiaowei Fei; Zehan Zhang; Ya‐nan Dou; Weihao Lv; Hongqing Chen; Li Wang; Xin He; Wangshu Chao; Peng Luo; Zhou Fei (Advanced Science)
Abstract Shockwave‐induced traumatic brain injury (TBI) results in the onset of post‐traumatic stress disorder (PTSD), triggered either by the TBI itself or other stressors. However, the interplay and underlying mechanisms of how these factors synergistically induce PTSD remain inadequately elucidated. Here, mice in the TBI (induced by biological shock tube blast injury) and PTSD (induced by single prolonged stress method) groups both displayed symptoms of PTSD behaviors, with the TBI+PTSD (composite model) group exhibiting more severe manifestations. The result of snRNA‐seq demonstrated a noticeable increase in the population of Gabra6+ neurons in the prefrontal cortex region of mice in the TBI+PTSD group. Knocking down cortical Gabra6 mitigated PTSD‐related behavioral outcomes. Mechanistically, the Smad3/4 complex activation led to the upregulation of Gabra6 expression in cortical neurons. Interaction of Gabra6 with Homer1 activated downstream cAMP signaling pathways. Homer1KO‐Nestin mice show reduced susceptibility to PTSD. Subsequently, the efficacy of monoclonal antibody intervention at the 218 site of Gabra6 in ameliorating PTSD development is verified. This study suggests that TBI and stressors act as independent components in PTSD development, with Gabra6+ neurons pivotal in synergistically facilitating PTSD formation. Strategies geared toward minimizing exposure to singular or combined stressors may effectively diminish the risk of developing PTSD.